Impedance-derived electrochemical capacitance spectroscopy for the evaluation of lectin-glycoprotein binding affinity - Santos, Adriano [UNESP]; Carvalho, Fernanda C. [UNESP]; Roque-Barreira, Maria-Cristina; Bueno, Paulo Roberto [UNESP] (Elsevier B.V., 2014)
Characterization of lectin-carbohydrate binding using label-free methods such as impedance-derived electrochemical capacitance spectroscopy (ECS) is desirable to evaluate specific interactions, for example, ArtinM lectin and horseradish peroxidase (HRP) glycoprotein, used here as a model for proteincarbohydrate binding affinity. An electroactive molecular film comprising alkyl ferrocene as a redox probe and ArtinM as a carbohydrate receptive center to target HRP was successfully used to determine the binding affinity between ArtinM and HRP. The redox capacitance, a transducer signal associated with the alkyl ferrocene centers, was obtained by ECS and used in the Langmuir adsorption model to obtain the affinity constant (1.6 +/- 0.6) x 10(8) L mol(-1). The results shown herein suggest the feasibility of ECS application for lectin glycoarray characterization. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ArtinM; HRP; Impedance-derived electrochemical capacitance spectroscopy; Langmuir isotherm; Binding affinity constant